Ramificação e distribuição dos nervos frênicos no músculo diafragma do gato doméstico - Moreira, Pamela Rodrigues Reina; Guimarães, Gregório Corrêa [UNESP]; Machado, Márcia Rita Fernandes [UNESP]; Santos, André Luiz Quagliatto; Gerbasi, Sílvia Helena Brendolan; Miglino, Maria Angélica (My University, 2007)
The ramification and the distribution of the phrenic nerves right and left had been studied in 30 muscles diaphragms of unknown breed adult domestic cats, 7 males and 23 females, and were fixed in 10% buffered formalin solution. After fixation and dissection, it was observed that the phrenic nerves ramified for the respective carnous parts of the muscle diaphragm, pars lumbalis, costalis and sternalis, and had finished in higher frequency in dorsolateral trunk and ventral branch (63.33%). We observed the following arrangements: dorsal, ventral and lateral branches (25.0%); dorsal branch and ventrolateral trunk (6.66%); dorsolateral and ventrolateral trunks (3.33%); dorsolateral trunk, lateral and ventral branches (1.66%). The phrenic nerves had distributed symmetrically in 11 samples (36.66%), only showing the termination in dorsolateral trunk and ventral branch. The dorsal branches supplied pars lumbalis (73.33% to right and 56.66% to the left) and pars costalis (13.33% to right and 10.0% to the left). The right dorsal branch supplied the crus mediale dexter of the right pillar (100.0%) and the left dorsal branch supplied the crus mediale sinister of the right pillar and the left pillar (100.0%). The lateral branches supply pars lumbalis (23.33% to right and 33.33% to the left), pars costalis (96.66% to right and 100.0% to the left) and pars sternalis (3.33% only to the right). The ventral branches supplied the ventral region of pars costalis (46.66 % to right and 43.33% to the left) and pars sternalis (96.66% to right and 100.0% to the left). Four female animals (13.33%) had shown fibers crossing proceeding from the left ventral branch for right antimere had been that in one of these samples (3.33%) occurred connection between the left ventral branch and the right.
Ramification and distribution of the phrenic nerves in the muscle diaphragm of the domestic cat
Keywords: Cat; Distribution; Phrenic nerve; Ramification; Animalia; Felis catus